Synthesis and metal complexation of a Schiff base derivative of 2-amino-4-(p-tolyl)thiazole - Sekerci, M; Alkan, C; Çukurovali, A (Interperiodica, 2000)
Thiazole Schiff bases and their metal complexes have shown good biological activity. In this work, a Schiff base has been synthesized from the reaction of 4-N,N-dimethylbenzaldehyde and 2-amino-4-(p-tolyl)thiazole. This compound was used as a complexing agent for Cu(II), Ni(II), and Co(II). The authenticity of the ligand and complexes was established by elemental analyses, UV-VIS, FT-IR, H-1 NMR, C-13 NMR, magnetic susceptibility measurements, TGA, and DTA. The nickel and cobalt compounds have square-planar and distorted octahedral structures, while the copper compound has a tetrahedral structure.
Keywords: Copper(Ii) Complexes